Including in an institution of higher education educational development. (Texas Journal of Philology, Culture and History, 2025)
The article discusses the need to introduce inclusive education in higher education institutions. National and international legal bases of inclusive education are studied and analyzed. In the author's article, the current situation of inclusive education in Uzbekistan's higher education institutions, as well as the factors hindering the introduction of this form of education, and a number of tasks for their elimination are determined. Necessary recommendations on the introduction of inclusive education in educational institutions, its effective integration and adaptation to the traditional form of education have been developed.